2016
DOI: 10.1007/s00406-016-0697-2
|View full text |Cite
|
Sign up to set email alerts
|

Negative symptoms and their association with depressive symptoms in the long-term course of schizophrenia

Abstract: Depressive symptoms abound in schizophrenia and even in subclinical states of the disorder. We studied the frequency of these symptoms and their relationship to negative symptoms from the first psychotic episode on over a long-term course of 134 months on data for 107 patients in our ABC Schizophrenia Study. Prevalence rates of 90 % for presenting at least one negative symptom and of 60 % for presenting at least one depressive symptom in the first psychotic episode illustrate the frequency of these syndromes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(45 citation statements)
references
References 57 publications
3
41
0
1
Order By: Relevance
“…The finding of an overall decrease in apathy levels in the long-term is in line with results from two previous follow-up studies from FEP [30] and first-admission schizophrenia participants [51]. In the FEP TIPS study, a group characterized by enduring high apathy levels was discernible in the second year of treatment.…”
Section: Development Of Apathy In Participants With Fepsupporting
confidence: 90%
“…The finding of an overall decrease in apathy levels in the long-term is in line with results from two previous follow-up studies from FEP [30] and first-admission schizophrenia participants [51]. In the FEP TIPS study, a group characterized by enduring high apathy levels was discernible in the second year of treatment.…”
Section: Development Of Apathy In Participants With Fepsupporting
confidence: 90%
“…Individuals at clinical high-risk for schizophrenia from the North American Prodrome Longitudinal Study (NAPLS) cohort have depressive symptoms that have been shown to be associated with negative symptoms (124). This association has also been reported in longitudinal data of patients with schizophrenia extending from the first episode to 10+ years of chronic psychosis (125). Furthermore, a recent meta-analysis reported a relationship between negative symptoms of schizophrenia and defeatist personal beliefs, a cognitive construct thought to underlie motivational deficits in individuals with depression (126).…”
Section: The Role Of Inflammation In Reward Processing Deficits In Psmentioning
confidence: 71%
“…10 Negative symptoms commonly appear during the prodromal phase of schizophrenia and before the first acute psychotic episode ( Figure 2). 2,[9][10][11] Among patients with negative symptoms, 73% had them before the onset of positive symptoms and 20% experienced them within the same month as positive symptoms. 11 Prodromal onset of negative symptoms has been characterized as a risk factor for the switch to psychosis 12,13 and it is associated with negative symptoms in the first psychotic episode.…”
Section: Negative Symptom Coursementioning
confidence: 99%
“…2,[9][10][11] Among patients with negative symptoms, 73% had them before the onset of positive symptoms and 20% experienced them within the same month as positive symptoms. 11 Prodromal onset of negative symptoms has been characterized as a risk factor for the switch to psychosis 12,13 and it is associated with negative symptoms in the first psychotic episode. 14 Negative symptoms can also present during the psychotic phase of illness, so clinicians should be mindful of positive symptoms that are accompanied by decreased emotional expression, social withdrawal, and functional deterioration.…”
Section: Negative Symptom Coursementioning
confidence: 99%